Dual roles of methylglyoxal in cancer - Wang, Zongao; Liu, Shaojun; Zhang, Minghui; Liu, Min (Frontiers in Oncology, 2025)
Cancer treatment currently includes a variety of approaches. Chemotherapy, targeted therapy, and immunotherapy are combined based on cancer characteristics to develop personalized treatment plans. However, drug resistance can hinder the progress of treatment over time. Methylglyoxal (MG) is a metabolite with hormesis, exhibiting both pro-tumor and anti-tumor actions depending on its concentration during cancer progression. The MG-related metabolic pathway is being explored in the development of anti-cancer drugs, focusing on reducing MG stress or exploiting its cytotoxic effects to inhibit cancer progression. This article investigates the dual role of MG in cancer, emphasizing its effects on cell metabolism and tumor progression. It proposes MG capture therapy for the pre-cancerous stage and MG toxicity therapy for the cancer stage, contributing to the development of precise and individualized cancer treatments.